The Southern Dutch Dialect Dictionaries - Kruijsen, Joep; van Keymeulen, Jacques (Lexikos, 1997)
The article on the three dictionaries of the southern Dutch dialects is divided into two parts. In the first part Joep Kruijsen (University of Nijmegen, The Netherlands) treats the history of the Woordenboek van de Brabantse Dialecten (Dictionary of the Brabant Dialects), the Woordenboek van de Limburgse Dialecten (Dictionary of the Limburg Dialects) and the Woordenboek van de Vlaamse Dialecten (Dictionary of the Flemish Dialects), three dictionaries which together record the vocabulary of the southern Dutch dialects. He describes the plan and method of collection and presentation. Because of the systematic arrangement (introduced by Weijnen) the three dictionaries are unique in Dutch and international lexicography. They combine a dictionary with a word atlas. In the second part of the article Jacques van Keymeulen (University of Ghent, Belgium) deals with a number of new methodological developments which were introduced following the start of the publication of part III General Vocabulary (apart from Part I Agricultural Terminology and Part II Nonagricultural Terminologies). After the institution of REWO (Regionale Woordenboeken), a coordinating body for the three dictionaries within the Dutch Language Union, and because of the introduction of sophisticated software, the databases can be combined to give a survey of the whole of the southern Dutch language area. Keywords: lexicography, onomasiology, dialect geography, language variation, phonology, historical linguistics, dictionary, regional dictionary, word atlas, cartography, general vocabulary, agrarian terminology, terminology of traditional crafts, dialect, traditional dialect, flemish, brabant dialect, limburg dialect, dutch, the netherlands, belgium, french flanders, methodology, systematical arrangement, automation, database, user groups, usefulness